2007
DOI: 10.1007/s00210-007-0213-3
|View full text |Cite
|
Sign up to set email alerts
|

Potassium channels are involved in testosterone-induced vasorelaxation of human umbilical artery

Abstract: Recent studies have shown that testosterone induces relaxation of different arteries, although the mechanism of this action is still under debate. We investigated the involvement of potassium channels in this mechanism. Using standard organ bath techniques, rings of human umbilical arteries (HUA) without endothelium were contracted by serotonin (5-HT, 1 microM), histamine (10 microM) and potassium chloride (KCl, 30 and 60 mM), and the vasorelaxant effect of testosterone was analysed. Testosterone (100 microM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
66
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 43 publications
12
66
0
Order By: Relevance
“…Therefore, it is reasonable to propose that 1) an insufficiency of androgens during pregnancy, particularly 5␤-DHT, could contribute, at least in part, to the development of preeclampsia/eclampsia and 2) exogenously administered 5␤-DHT may be therapeutically relevant for the treatment of gestational HT. Not only does Tes induce similar vasorelaxation in isolated vessels from women (2,48,55,71), but the female vasculature is also acutely sensitive to AR-independent vasodilation induced by 5␤-DHT (48), which also increases its potential for use as a safe antihypertensive in women.…”
Section: Physiological Relevancementioning
confidence: 94%
See 2 more Smart Citations
“…Therefore, it is reasonable to propose that 1) an insufficiency of androgens during pregnancy, particularly 5␤-DHT, could contribute, at least in part, to the development of preeclampsia/eclampsia and 2) exogenously administered 5␤-DHT may be therapeutically relevant for the treatment of gestational HT. Not only does Tes induce similar vasorelaxation in isolated vessels from women (2,48,55,71), but the female vasculature is also acutely sensitive to AR-independent vasodilation induced by 5␤-DHT (48), which also increases its potential for use as a safe antihypertensive in women.…”
Section: Physiological Relevancementioning
confidence: 94%
“…Figure 1 summarizes the possible nongenomic mechanisms of androgen action on the vascular wall. A variety of studies has demonstrated that the key mechanism underlying the vasorelaxing action of Tes is associated with the modulation of VSM cell membrane ion channel function, particularly 1) inactivation of L-type voltage-operated Ca 2ϩ channels (VOCCs) (6, 13, 17, 23, 24, 41-43, 48, 50, 59) or 2) activation of K ϩ channels (2,3,8,10,19,60,64,68,71,73), particularly the voltage-operated K ϩ channel (K v ) and/or the large-conductance Ca 2ϩ -activated K ϩ channel (BK Ca ).…”
Section: Mechanisms Of Androgen-induced Vasodilationmentioning
confidence: 99%
See 1 more Smart Citation
“…The vasorelaxant effects of testosterone on human umbilical arteries, pre-contracted with serotonin or histamine or potassium chloride, were partially mediated by the activation of both voltage-sensitive K C channels and large-conductance, Ca 2C -activated K C channels (Cairrão et al 2008). This supports earlier animal studies that suggest that testosterone-induced vasorelaxation is mediated predominantly via K C channels in rat mesenteric arterial beds (Tep-areenan et al 2002), rabbit coronary arteries (Yue et al 1995) and rat aorta (Ding & Stallone 2001).…”
Section: Vascular Mechanisms Of Testosteronementioning
confidence: 99%
“…[106][107][108] The involvement of potassium channels in testosterone-induced vasodilatation has also been studied by many researchers. [109][110][111] Cairrao et al 112 reported that an AR antagonist, flutamide, and an adenosine triphosphate-sensitive potassium-channel inhibitor, glibenclamide, had no influence on the testosterone relaxant effect, whereas a voltage-sensitive potassium-channel inhibitor, 4-aminopyridine, decreased this effect of testosterone. Opening of voltage-sensitive potassium channels induces hyperpolarization of the plasma membrane, which in turn may lead to the closing of L-type Ca2+ channels.…”
Section: Effects Of Testosterone On Ecsmentioning
confidence: 99%